Analysis of single and team kayak acceleration - Gomes, B.; Viriato, N.; Sanders, R.; Conceicao, F.; Vaz, M.; Vilas-Boas, J. P. (ISBS - Conference Proceedings Archive (Konstanz), 2011)
The purpose of this study was to gain more insights about 3D acceleration patterns in kayaks with different numbers of paddlers. Four female international level paddlers participated in this study. A tri-axial accelerometer was positioned on the deck of the kayaks. The paddlers were tested in kayaks of one, two and four athletes. The acceleration data were observable in real time as well as stared for subsequent analysis. Results suggested a similar vertical and lateral acceleration-time pattern curve for the three kayaks in the study. The shape of the curve of acceleration in the direction of travel was different for the kayaks with single paddlers from those of the kayaks with two and four paddlers.